(3cJGH aj eYQaI GdCfZGe hGdgfhc hGdWQH aj GdEKfi YTQ hGdSJIs
(3ChdgG (B:s
(3GdMeO ddg GdPi ChLH hLhH hGLH EjLGH aJM HGH SHH CSHGH WdH LdH GdeWQH Edi Ybhd CQHGHg s
(3BNQgG (B:s
(3hdYf Gddg ef jYde gPg GdOGFQI dCeQCg hdCMeb hdYf Gddg def jHNd Hg Ydi Cgdg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B47s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B66 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK HGSJGfHhd (B(2130) s
Keywords: (3GdehSjbi hGdZfGAs